Odpowiedź :
Odpowiedź:
tu masz wszystko rozpisane
mam nadzieję, że dobrze :3
a) 2x + 17 = 26 - x | - 17
2x = 9 - x | + x
3x = 9 | : 3
x = 3
b) 11 - x = 3x +8 | + x
11 = 4x + 8 | - 8
3 = 4x | : 4
3/4 = x
c) -7 (x + 2) + 4 = -3x
-7x - 14 + 4 = -3x
-7x - 10 = -3x | + 7x
-10 = 4x | : 4
-2,5 = x
d) -4 (1/2x -2) - 4 = 2(-x + 2)
-2x + 8 - 4 = -2x + 4
-2x + 4 = -2x + 4
równanie tożsamościowe
(każda liczba spełnia to równanie)
e) 2x (x - 1) = 2(x - 1)(x + 3)
2x^2 - 2x = (2x - 2)(x + 3)
2x^2 - 2x = 2x^2 + 6x - 2x -6
2x^2 - 2x = 2x^2 + 4x - 6 | - 2x^2
-2x = 4x - 6 | - 4x
-6x = -6 | : (-6)
x = 6
f) (3x + 2)(2x + 1) = (6x - 3)(x + 1)
6x^2 + 3x + 4x + 2 = 6x^2 + 6x - 3x - 3
6x^2 + 7x + 2 = 6x^2 + 3x - 3 | - 6x^2
7x + 2 = 3x - 3 | - 3x
4x + 2 = -3 | - 2
4x = - 5 | : 5
x = 1/4
Wyjaśnienie:
Matematyka